Low-carbon concrete based on fine sand and lithium slag comprehensive utilization and preparation method thereof

CN122958124APending Publication Date: 2026-10-23SICHUAN HONGYE COMMODITY CONCRETE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611113015.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-25
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]为了解决传统混凝土材料成本高、环境污染严重的问题,本申请提供一种基于精品砂和锂渣综合利用的低碳混凝土及制备方法

Benefits of technology

1、由于本申请采用700-800份精品砂奠定混凝土稳定基础,100-150份废弃石粉与120-150份锂渣实现工业废弃物再利用,降低天然骨料依赖与资源开采量,契合低碳理念;锂渣因特定成分限定具备良好火山灰活性,与水泥水化产物二次反应生成凝胶,填充孔隙、细化结构,增强混凝土力学强度与耐久性,延长使用寿命。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the field of concrete, and particularly discloses a low-carbon concrete based on comprehensive utilization of exquisite sand and lithium slag and a preparation method. The low-carbon concrete based on comprehensive utilization of exquisite sand and lithium slag comprises, in terms of weight parts, 150-200 parts of cement, 700-800 parts of exquisite sand, 100-150 parts of stone powder, 120-150 parts of lithium slag, 1-2.5 parts of a water reducing agent, 1000-1200 parts of coarse aggregate and 60-70 parts of water. The stone powder is selected from waste stone powder in a stone processing industry. The lithium slag contains 0.5-2.0% of lithium oxide and the total content of silicon dioxide and aluminum oxide is greater than or equal to 60%. The low-carbon concrete based on comprehensive utilization of exquisite sand and lithium slag has the advantages of low manufacturing cost and low carbon environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of concrete, and more specifically, to a low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag, and a method for its preparation. Background Technology

[0002] Traditional concrete uses cement as its core binder, and cement production is extremely complex and costly. The process of converting raw materials such as limestone and clay into cement clinker through crushing, grinding, and calcination consumes a large amount of fossil fuels. For example, the high-temperature calcination stage typically requires heating materials to around 1450°C. The extensive use of fuels such as coal and natural gas in this process not only results in energy costs accounting for 40%-60% of cement production costs but also makes cement prices significantly susceptible to fluctuations in the energy market. Furthermore, the booming construction industry has led to a continuous increase in demand for cement, and the resulting supply shortage has further driven up cement prices, thus significantly increasing the material costs of concrete.

[0003] Cement production is a major source of carbon dioxide emissions. Approximately one ton of carbon dioxide is emitted for every ton of cement clinker produced, and the cement industry accounts for 7%-8% of global anthropogenic carbon emissions. These large amounts of carbon dioxide emissions exacerbate the global greenhouse effect and pose a serious threat to the ecological environment. Furthermore, dust emissions from cement production cannot be ignored. Kilns, mills, and other equipment generate large amounts of dust-laden exhaust gas during operation. If this dust is released directly into the atmosphere without effective treatment, it will not only reduce air quality and affect the health of nearby residents, but may also contribute to environmental problems such as smog.

[0004] Overexploitation of natural sand has led to severe ecological damage. Extensive mining of natural sand from rivers and beaches has disrupted natural landforms, causing river deformation, coastal erosion, and consequently impacting aquatic habitats and disrupting the ecological balance. The production of manufactured sand, if environmental protection measures are inadequate, can also generate dust pollution, and its high energy consumption further exacerbates energy depletion and carbon emissions. Furthermore, after concrete is disposed of, its complex composition makes recycling difficult, resulting in large quantities of waste concrete being landfilled or stockpiled, occupying significant land resources. Moreover, harmful substances in concrete may seep into the soil and groundwater, polluting soil and aquatic environments.

[0005] Faced with the dual challenges of high cost and serious environmental pollution from traditional concrete materials, it is urgent to develop a low-carbon concrete preparation method based on the comprehensive utilization of high-quality sand and lithium slag. This is of great significance for reducing construction costs and improving the ecological environment. Summary of the Invention

[0006] To address the problems of high cost and severe environmental pollution associated with traditional concrete materials, this application provides a low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag, and its preparation method.

[0007] This application provides a low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag, employing the following technical solution: A low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag comprises, by weight, 150-200 parts cement, 700-800 parts high-quality sand, 100-150 parts stone powder, 120-150 parts lithium slag, 1-2.5 parts water-reducing agent, 1000-1200 parts coarse aggregate, and 60-70 parts water. The stone powder is selected from waste stone powder in the stone processing industry, and the lithium slag contains 0.5-2.0% lithium oxide and ≥60% total silica and alumina.

[0008] By adopting the above technical solution and using 700-800 parts of high-quality sand, its excellent performance provides a stable foundation for concrete. Simultaneously, the addition of 100-150 parts of waste stone powder from stone processing and 120-150 parts of lithium slag allows for the reuse of industrial waste. The filling effect of the stone powder optimizes the microstructure of the concrete, while the lithium slag participates in chemical reactions to enhance performance. Both reduce dependence on natural sand, stone, and other aggregates, thus reducing resource extraction at the source. Traditional concrete production involves high energy consumption and carbon emissions from natural aggregate mining and cement manufacturing. This formula utilizes industrial waste, reducing the production of new raw materials and lowering energy consumption and carbon emissions, aligning with the low-carbon and environmentally friendly concept. Strict limits on the lithium oxide content (0.5-2.0%) and the total content of silica and alumina (≥60%) in the lithium slag ensure its good pozzolanic activity. In the alkaline environment of concrete, the active components of the lithium slag can undergo a secondary reaction with the calcium hydroxide produced during cement hydration. The gel substances generated by the secondary reaction, such as calcium silicate gel, fill the pores inside the concrete, refine the pore structure, and enhance the density of the concrete's internal structure. This not only improves the concrete's compressive and tensile mechanical strength but also effectively prevents external corrosive media, such as chloride ions and sulfate ions, from entering the concrete, thereby improving its durability and extending its service life.

[0009] Optionally, the fine sand has a particle size range of 0.15-5mm, a fineness modulus of 2.6-3.0, and a mud content of ≤1.0%.

[0010] By adopting the above technical solutions, the reasonable limitation of the particle size range and fineness modulus of high-quality sand ensures that its particle size distribution is close to the ideal state. In concrete, particles of different sizes fill each other, with coarse particles forming a skeleton and fine particles filling the gaps, reducing porosity, increasing bulk density, and providing good stability for concrete. The low mud content of high-quality sand ensures its purity and reduces the negative impact of mud on cement hydration and the bonding between aggregate and cement paste. At the same time, the regular particle shape allows for better interlocking in concrete, improving the cohesiveness and water retention of the concrete mixture, avoiding segregation and bleeding, and improving the workability of concrete. Under stress, the good particle shape and dense packing structure make the stress distribution more uniform, enhancing the mechanical strength of concrete, such as compressive strength and flexural strength.

[0011] Optionally, the coarse aggregate has a particle size of 5-25 mm and a content of needle-like and flaky particles ≤15%.

[0012] By adopting the above technical solution, the coarse aggregate particle size (5-25mm) meets the requirements for concrete skeleton construction and forms a reasonable gradation system when combined with high-quality sand. Large-diameter coarse aggregate bears the main load, while small-diameter coarse aggregate fills the voids, stabilizing the internal structure of the concrete, effectively transferring and dispersing loads, and improving the concrete's load-bearing capacity. The low content of needle-like and flaky particles ensures the regular shape of the coarse aggregate. Needle-like and flaky particles easily cause stress concentration in concrete under stress, leading to premature cracking and failure. The low content of needle-like and flaky particles increases the contact points and contact area between coarse aggregates, resulting in a more uniform stress distribution, improving the compressive and flexural strength of the concrete, enhancing the stability of the concrete structure during long-term use, and reducing the risk of structural failure.

[0013] Optionally, the lithium slag is subjected to high-temperature alkaline fusion treatment, and the specific method of high-temperature alkaline fusion treatment is as follows: Lithium slag and sodium carbonate are mixed and ground at a mass ratio of 1:(4-6). The mixture is then transferred to a heating device and heated to 850-950℃ at a heating rate of 5-10℃ / min. The temperature is maintained for 1-3 hours. After the reaction is completed, the mixture is cooled to 300-400℃ in the furnace and then allowed to cool naturally to room temperature in the air.

[0014] By employing the above-mentioned technical solution, lithium slag and sodium carbonate are mixed at a mass ratio of 1:(4-6), and subjected to high-temperature alkali fusion treatment at 5-10℃ / min, raising the temperature to 850-950℃ and maintaining the temperature for 1-3 hours. This effectively breaks down the original stable crystal structure of the lithium slag. At high temperatures, sodium carbonate reacts chemically with the minerals in the lithium slag, causing the internal chemical bonds of the lithium slag to break and recombine. The originally inert aluminosilicates and other components are transformed into more active amorphous substances, significantly increasing the number of active sites. The treated lithium slag can react more fully with cement hydration products in concrete, generating more gel substances, further filling the internal pores of the concrete, making the pore structure more refined and uniform. This not only significantly improves the later-stage strength of the concrete, continuously enhancing its load-bearing capacity during long-term use, but also enhances the concrete's impermeability, effectively preventing the penetration of water and harmful ions, improving the concrete's resistance to chemical erosion, such as acid rain and seawater, and extending the service life of concrete structures in harsh environments.

[0015] Optionally, the coarse aggregate may be selected from crushed concrete waste.

[0016] By adopting the above technical solution and using crushed concrete waste as coarse aggregate, a large amount of construction waste can be recycled and processed. If this waste is not recycled, its indiscriminate dumping will occupy a significant amount of land resources, and harmful substances may seep into the soil and groundwater, causing environmental pollution. Recycling waste reduces this environmental risk and achieves a closed-loop resource cycle. Using waste concrete to replace natural coarse aggregate reduces the mining and transportation costs of natural aggregate. Natural aggregate resources are becoming increasingly scarce and their prices are constantly rising, while waste recycling and processing costs are relatively low, effectively reducing the raw material costs of concrete production, improving the economic efficiency of enterprises, and also promoting the sustainable development of the construction industry.

[0017] Optionally, the coarse aggregate undergoes surface treatment, and the surface treatment method for the coarse aggregate is as follows: Wash and dry the coarse aggregate, then add it to a 2-5% (w / w) γ-aminopropyltriethoxysilane solution and soak for 160-180 minutes. After soaking, transfer the coarse aggregate to a drying equipment and dry it at 50-60℃. A nano-calcium carbonate suspension with a mass concentration of 1-5% was sprayed onto the surface of the dried coarse aggregate. The nano-calcium carbonate suspension also contained sodium hexametaphosphate with a mass concentration of 0.5-1%. After spraying, the coarse aggregate was allowed to air dry naturally.

[0018] By employing the above technical solution, after cleaning and drying, the coarse aggregate is soaked in a γ-aminopropyltriethoxysilane solution. The siloxy group at one end of the silane coupling agent molecule reacts chemically with the hydroxyl groups on the surface of the coarse aggregate to form a strong covalent bond, while the aminopropyl organic functional group at the other end can undergo physical adsorption or chemical reaction with the hydration products in the cement paste, forming a chemical bridge between the aggregate and the cement paste, significantly enhancing interfacial adhesion. A nano-calcium carbonate suspension is sprayed onto the surface of the coarse aggregate. The extremely small particle size of the nano-calcium carbonate fills the tiny pores on the aggregate surface, increasing surface roughness and improving surface activity. Simultaneously, sodium hexametaphosphate acts as a dispersant, ensuring uniform dispersion of the nano-calcium carbonate for better performance. This treatment significantly improves the tensile and shear strength of the concrete because the strong adhesion between the aggregate and the cement paste effectively resists tensile and shear forces, while also enhancing concrete durability and delaying performance degradation caused by interfacial damage.

[0019] Optionally, the water-reducing agent comprises 30-40 parts by weight of polycarboxylate-based water-reducing agent mother liquor, 5-10 parts of sodium gluconate, 10-15 parts of sodium lignosulfonate, and 35-45 parts of water.

[0020] By adopting the above technical solutions, polycarboxylate superplasticizer mother liquor, with its unique molecular structure, can disperse cement particles in concrete through electrostatic repulsion and steric hindrance, effectively reducing the water consumption of concrete. While ensuring the workability of concrete, it reduces the water-cement ratio and improves concrete strength and durability. Sodium gluconate has retarding properties, slowing down the cement hydration reaction and extending the concrete setting time, providing more working time for concrete construction and preventing premature setting from affecting construction quality. It also has a certain water-reducing effect, working synergistically with the polycarboxylate superplasticizer mother liquor. Sodium lignosulfonate, as an environmentally friendly dispersant, helps the polycarboxylate superplasticizer better disperse cement particles, improving the dispersibility of the superplasticizer, and its low cost reduces the overall production cost of the superplasticizer. The synergistic effect of all components ensures good concrete workability while reducing the cost of the superplasticizer, thereby improving the cost-effectiveness of concrete and enabling it to meet engineering quality requirements while achieving better economic benefits.

[0021] Secondly, this application provides a method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag, employing the following technical solution: A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag includes the following steps: Mix coarse aggregate and fine sand for 1-2 minutes, then add cement, stone powder and lithium slag, and mix for 5-10 minutes to obtain dry material. Add water-reducing agent and water to the dry material and mix for 10-15 minutes.

[0022] In summary, this application has the following beneficial effects: 1. This application uses 700-800 parts of high-quality sand to lay a stable foundation for concrete, and 100-150 parts of waste stone powder and 120-150 parts of lithium slag to reuse industrial waste, reducing reliance on natural aggregates and resource extraction, which is in line with the low-carbon concept. Due to its specific composition, lithium slag has good pozzolanic activity, which reacts with cement hydration products to form a gel, filling pores, refining the structure, enhancing the mechanical strength and durability of concrete, and extending its service life.

[0023] 2. In this application, lithium slag and sodium carbonate are preferably mixed and ground at a mass ratio of 1:(4-6), and then subjected to high-temperature alkali fusion treatment by heating at 5-10℃ / min to 850-950℃ and holding the temperature for 1-3 hours. This process breaks down the crystal structure of the lithium slag, promotes the rearrangement of internal chemical bonds, transforms inert components into more reactive amorphous substances, and increases the number of active sites. The lithium slag treated in this way can fully react with cement hydration products in concrete, generating more gel to refine the pore structure, significantly improving the later-stage strength of concrete, enhancing its impermeability and chemical erosion resistance, and extending its service life in harsh environments.

[0024] 3. The preferred technical solution in this application is to use crushed concrete waste as coarse aggregate and perform surface treatment. This not only realizes the recycling and treatment of construction waste, reduces land occupation and environmental pollution, reduces dependence on natural aggregates and mining and transportation costs, improves the economic benefits of enterprises, and promotes the sustainable development of the construction industry, but also enhances the interfacial adhesion between coarse aggregate and cement paste, fills pores, improves surface activity, significantly improves the tensile and shear strength of concrete, enhances durability, and delays performance degradation through immersion in γ-aminopropyltriethoxysilane solution and spraying with nano-calcium carbonate suspension. Detailed Implementation

[0025] The following detailed description of this application is provided in conjunction with the embodiments. It should be noted that: unless otherwise specified, the conditions in the following embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following embodiments are all from commercially available sources.

[0026] Preparation Example 1 A method for high-temperature alkaline fusion treatment of lithium slag: The lithium slag is selected with a lithium oxide content of 0.5%-2.0% and a total silica and alumina content of ≥60%. The lithium slag is washed with water and then dried to reduce its moisture content to below 1%. Industrial-grade sodium carbonate with a purity of ≥98% is selected. Lithium slag and sodium carbonate are mixed at a mass ratio of 1:5. The mixed lithium slag and sodium carbonate are placed into the grinding jar of a ball mill, and grinding balls with a diameter of 10 mm are added at the same time. The amount of grinding balls added is 30% of the volume of the grinding jar. The grinding time is 60 minutes and the rotation speed is 300 r / min. After grinding, transfer the uniformly mixed material to a corundum crucible, place the crucible containing the material into a high-temperature resistance furnace preheated to 150°C, set the heating rate to 5-10°C / min, and heat to 900°C. When the temperature reaches the set target temperature, maintain the constant temperature reaction for 2 hours. After the reaction is complete, turn off the power to the heating equipment and allow the crucible to cool to 350°C inside the furnace. Then, remove the crucible and place it in a well-ventilated area to cool naturally to room temperature (25°C). The cooled product is the lithium slag that has undergone high-temperature alkali fusion treatment.

[0027] Preparation Example 2 A method for high-temperature alkaline fusion treatment of lithium slag: the difference from preparation example 1 is that lithium slag and sodium carbonate are mixed at a mass ratio of 1:4.

[0028] Preparation 3 A method for high-temperature alkaline melting treatment of lithium slag: the difference from preparation example 1 is that lithium slag is mixed with sodium carbonate at a mass ratio of 1:6.

[0029] Preparation 4 A method for high-temperature alkaline melting treatment of lithium slag: The difference from Preparation Example 1 is that after the reaction is completed, the power supply of the heating equipment is turned off, and the crucible is allowed to cool to room temperature of 25°C in the furnace.

[0030] Preparation 5 A method for high-temperature alkaline fusion treatment of lithium slag: The difference from Preparation Example 1 is that after the reaction is completed, the power supply of the heating equipment is turned off, the crucible is taken out and placed in a well-ventilated place to allow it to cool naturally in the air to room temperature of 25°C.

[0031] Preparation Example 6 A surface treatment method for coarse aggregate is as follows: Pour the coarse aggregate into a drum washing machine and wash for 30 minutes until there is no obvious dirt, dust or other impurities on the surface of the coarse aggregate. Then use a hot air drying oven, set the temperature to 100℃ and dry for 4 hours. Weigh 35 kg of γ-aminopropyltriethoxysilane and add deionized water to a final volume of 1000 kg. Slowly pour 500 kg of dried coarse aggregate into the soaking container, ensuring that the coarse aggregate is completely submerged in the silane solution. Soak for 170 minutes, stirring the solution every 30 minutes during this time. After soaking, the coarse aggregate is removed from the solution and placed in a hot air drying oven. The temperature is set to 60℃ and the drying time is 3 hours. A nano-calcium carbonate suspension was prepared with a calcium carbonate concentration of 3% and a sodium hexametaphosphate concentration of 0.8%. The suspension was ultrasonically treated for 20 minutes using an ultrasonic dispersion device to ensure that the nano-calcium carbonate was uniformly dispersed in the suspension without agglomeration. A high-pressure spray gun was selected as the spraying equipment, with a spray gun pressure of 0.5 MPa. 50 kg of nano calcium carbonate suspension was evenly sprayed onto the surface of the coarse aggregate. After spraying, the coarse aggregate was allowed to air dry naturally in a well-ventilated environment.

[0032] Preparation Example 7 A surface treatment method for coarse aggregate is as follows: the difference from preparation example 6 is that 20 kg of γ-aminopropyltriethoxysilane is weighed and deionized water is added to make up to 1000 kg.

[0033] Preparation Example 8 A surface treatment method for coarse aggregate is as follows: the difference from preparation example 6 is that 50 kg of γ-aminopropyltriethoxysilane is weighed and deionized water is added to make up to 1000 kg.

[0034] Preparation Example 9 A surface treatment method for coarse aggregate is as follows: the difference from preparation example 6 is that a nano calcium carbonate suspension is prepared, wherein the concentration of calcium carbonate in the suspension is 1% and the concentration of sodium hexametaphosphate is 0.8%.

[0035] Preparation Example 10 A surface treatment method for coarse aggregate is as follows: the difference from preparation example 6 is that a nano calcium carbonate suspension is prepared, wherein the concentration of calcium carbonate in the suspension is 5% and the concentration of sodium hexametaphosphate is 0.8%. Example

[0036] Example 1 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag: Prepare 180kg silicate cement, 750kg high-quality sand, 130kg stone powder, 140kg lithium slag, 2kg water-reducing agent, 1100kg coarse aggregate, and 65kg water. The stone powder is waste stone powder from the stone processing industry. The lithium slag contains 0.5-2.0% lithium oxide and ≥60% total silica and alumina. The high-quality sand has a particle size range of 0.15-5mm, a fineness modulus of 2.6-3.0, and a mud content ≤1.0%. The coarse aggregate is crushed concrete waste with a particle size of 5-25mm and a needle-like / flaky particle content ≤15%. The water-reducing agent is prepared by mixing 3.5kg of polycarboxylate-based water-reducing agent mother liquor, 0.8kg of sodium gluconate, 1.2kg of sodium lignosulfonate, and 4kg of water. After thorough mixing, 2kg of the mixture is used as the water-reducing agent in this embodiment.

[0037] Mix coarse aggregate and fine sand for 1-2 minutes, then add cement, stone powder and lithium slag, and mix for 5-10 minutes to obtain dry material. Add water-reducing agent and water to the dry material and mix for 10-15 minutes to obtain concrete.

[0038] Example 2 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that: Prepare 150kg silicate cement, 700kg high-quality sand, 100kg stone powder, 120kg lithium slag, 1kg water-reducing agent, 1000kg coarse aggregate and 60kg water.

[0039] Example 3 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that: Prepare 200kg silicate cement, 800kg high-quality sand, 150kg stone powder, 150kg lithium slag, 2.5kg water-reducing agent, 1200kg coarse aggregate and 70kg water.

[0040] Example 4 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that the lithium slag is obtained from Example 1 by high-temperature alkali fusion treatment.

[0041] Example 5 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that the lithium slag is obtained from Preparation Example 2 by high-temperature alkali fusion treatment.

[0042] Example 6 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that the lithium slag is obtained from Preparation Example 3 by high-temperature alkali fusion treatment.

[0043] Example 7 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that: the coarse aggregate is selected from crushed concrete waste, and the coarse aggregate undergoes the surface treatment process described in Example 6.

[0044] Example 8 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that: the coarse aggregate is selected from crushed concrete waste, and the coarse aggregate undergoes the surface treatment process described in Example 7.

[0045] Example 9 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that: the coarse aggregate is selected from crushed concrete waste, and the coarse aggregate undergoes the surface treatment process described in Example 8.

[0046] Example 10 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that: the coarse aggregate is selected from crushed concrete waste, and the coarse aggregate undergoes the surface treatment process described in Example 9.

[0047] Example 11 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that: the coarse aggregate is selected from crushed concrete waste, and the coarse aggregate undergoes the surface treatment process described in Preparation Example 10.

[0048] Example 12 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that: the water-reducing agent is made by mixing 3 kg of polycarboxylate-based water-reducing agent mother liquor, 0.5 kg of sodium gluconate, 1 kg of sodium lignosulfonate and 3.5 kg of water, and taking 2 kg of the mixture as the water-reducing agent in this example.

[0049] Example 13 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that: the water-reducing agent is made by mixing 4 kg of polycarboxylate-based water-reducing agent mother liquor, 1 kg of sodium gluconate, 1.5 kg of sodium lignosulfonate and 4.5 kg of water, and after mixing evenly, 2 kg is taken as the water-reducing agent in this example.

[0050] Comparative Example 1 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that the lithium oxide content in the lithium slag is 0.1-0.5%.

[0051] Comparative Example 2 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 1 in that the total content of silica and alumina in the lithium slag is <60%. Comparative Example 3 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 4 in that the lithium slag is obtained from Example 4 by high-temperature alkali fusion treatment.

[0052] Comparative Example 4 A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag differs from Example 4 in that the lithium slag is obtained from Preparation Example 5 by high-temperature alkali fusion treatment.

[0053] The concrete prepared in the examples and comparative examples was made into concrete test blocks of 120*120*120cm, and its compressive strength was measured on the 7th day and the 28th day under standard curing.

[0054] Table 1 Experimental Data Example 1 8.20 47.52 Example 2 7.37 46.55 Example 3 7.48 46.89 Example 4 9.51 49.00 Example 5 8.79 48.08 Example 6 9.38 48.53 Example 7 9.85 49.56 Example 8 9.30 48.19 Example 9 9.69 49.32 Example 10 9.34 48.90 Example 11 9.58 49.18 Example 12 8.09 47.95 Example 13 7.86 47.76 Comparative Example 1 6.56 44.92 Comparative Example 2 6.01 43.60 Comparative Example 3 8.24 47.84 Comparative Example 4 8.58 47.59 Combining Example 1 and Comparative Examples 1-2 with Table 1, it can be seen that in Example 1, the lithium slag had a lithium oxide content of 0.5-2.0%, a total silica and alumina content ≥60%, a 7-day compressive strength of 8.20 MPa, and a 28-day compressive strength of 47.52 MPa. In Comparative Example 1, the lithium slag had a lithium oxide content of 0.1-0.5%, and in Comparative Example 2, the total silica and alumina content was <60%. The 7-day compressive strengths for Comparative Example 1 were 6.56 MPa and 6.01 MPa, respectively, and the 28-day compressive strengths were 44.92 MPa and 43.60 MPa, respectively. This indicates that lithium slag meeting specific composition requirements, due to its good pozzolanic activity, can fully react with cement hydration products, generating more gel substances to fill pores and significantly improving the compressive strength of concrete. When the lithium slag composition does not meet the standards, the reactivity is insufficient, failing to effectively strengthen the concrete structure, leading to a decrease in strength.

[0055] Combining Example 4 and Comparative Examples 3-4 with Table 1, it can be seen that the lithium slag of Example 4, after high-temperature alkali fusion treatment (cooled to 350°C in the furnace and then naturally cooled), has a 7-day compressive strength of 9.51 MPa and a 28-day compressive strength of 49.00 MPa. The lithium slag of Comparative Example 3, after treatment with Example 4 (cooled to 25°C in the furnace), and the lithium slag of Comparative Example 4, after treatment with Example 5 (directly naturally cooled to 25°C), have 7-day compressive strengths of 8.24 MPa and 8.58 MPa, and 28-day compressive strengths of 47.84 MPa and 47.59 MPa, respectively. A reasonable high-temperature alkali fusion treatment and cooling method can fully activate the lithium slag activity, optimize its microstructure, and allow the lithium slag to better participate in the reaction in concrete, thus improving its strength. An inappropriate cooling method will affect the activation effect of the lithium slag activity, thereby reducing the increase in concrete strength.

[0056] Based on Examples 1-3 and Table 1, it can be seen that when using 180kg, 150kg, and 200kg of cement respectively, the 7-day compressive strengths were 8.20MPa, 7.37MPa, and 7.48MPa, and the 28-day compressive strengths were 47.52MPa, 46.55MPa, and 46.89MPa, respectively. Changes in cement dosage have a certain impact on concrete strength. Within a certain range, increasing the cement dosage improves early strength, but the improvement is not significant, and excessive cement dosage has a poor effect on later strength improvement. This indicates that in this low-carbon concrete formula, cement dosage is not the only key factor determining strength; other components such as lithium slag and high-quality sand work synergistically with cement to jointly affect concrete performance.

[0057] Combining Examples 1 and 4-6 with Table 1, it can be seen that in Example 1, without high-temperature alkali fusion treatment of the lithium slag, the 7-day compressive strength was 8.20 MPa, and the 28-day compressive strength was 47.52 MPa. In Examples 4-6, the lithium slag was treated with high-temperature alkali fusion (different lithium slag to sodium carbonate mass ratios) as described in Examples 1-3, resulting in 7-day compressive strengths of 9.51 MPa, 8.79 MPa, and 9.38 MPa, and 28-day compressive strengths of 49.00 MPa, 48.08 MPa, and 48.53 MPa, respectively. High-temperature alkali fusion treatment significantly improves concrete strength. Different lithium slag to sodium carbonate mass ratios produce varying effects on strength improvement, but all are superior to untreated lithium slag, indicating that this treatment method effectively activates the lithium slag and enhances its contribution to concrete strength.

[0058] Combining Examples 1 and 7-11 with Table 1, it can be seen that in Example 1, the coarse aggregate without specific surface treatment had a 7-day compressive strength of 8.20 MPa and a 28-day compressive strength of 47.52 MPa. In Examples 7-11, the coarse aggregate, after different surface treatments (different concentrations of silane coupling agent and nano-calcium carbonate suspension), had 7-day compressive strengths between 9.30 and 9.85 MPa and 28-day compressive strengths between 48.19 and 49.56 MPa. Surface treatment of coarse aggregate can enhance its interfacial bond with cement paste and improve the compressive strength of concrete. Different treatment process parameters affect the strength improvement effect; appropriate concentrations of silane coupling agent and nano-calcium carbonate suspension can better exert the strengthening effect.

[0059] Combining Examples 1 and 12-13 with Table 1, it can be seen that the water-reducing agent in Example 1, composed of a specific ratio of polycarboxylate-based water-reducing agent mother liquor, sodium gluconate, sodium lignosulfonate, and water, exhibits a 7-day compressive strength of 8.20 MPa and a 28-day compressive strength of 47.52 MPa. Examples 12-13, with different proportions of water-reducing agent components, show 7-day compressive strengths of 8.09 MPa and 7.86 MPa, and 28-day compressive strengths of 47.95 MPa and 47.76 MPa, respectively. Variations in the proportions of water-reducing agent components have a certain impact on concrete strength. A reasonable water-reducing agent formulation can, while ensuring the workability of concrete, influence cement hydration and the bond between aggregates and cement paste to a certain extent, thus affecting strength.

[0060] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag, characterized in that, Its components, by weight, include 150-200 parts cement, 700-800 parts high-quality sand, 100-150 parts stone powder, 120-150 parts lithium slag, 1-2.5 parts water-reducing agent, 1000-1200 parts coarse aggregate, and 60-70 parts water. The stone powder is selected from waste stone powder in the stone processing industry. The lithium slag contains 0.5-2.0% lithium oxide and ≥60% total silica and alumina.

2. The low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag according to claim 1, characterized in that: The high-quality sand has a particle size range of 0.15-5mm, a fineness modulus of 2.6-3.0, and a mud content of ≤1.0%.

3. The low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag according to claim 1, characterized in that: The coarse aggregate has a particle size of 5-25mm and a content of needle-like and flaky particles ≤15%.

4. The low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag according to claim 1, characterized in that: The lithium slag is subjected to high-temperature alkaline fusion treatment, and the specific method of the high-temperature alkaline fusion treatment is as follows: Lithium slag and sodium carbonate are mixed and ground at a mass ratio of 1:(4-6). The mixture is then transferred to a heating device and heated to 850-950℃ at a heating rate of 5-10℃ / min. The temperature is maintained for 1-3 hours. After the reaction is completed, the mixture is cooled to 300-400℃ in the furnace and then allowed to cool naturally to room temperature in the air.

5. The low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag according to claim 1, characterized in that: The coarse aggregate is selected from crushed concrete waste.

6. The low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag according to claim 5, characterized in that: The coarse aggregate undergoes surface treatment, and the surface treatment method for the coarse aggregate is as follows: Wash and dry the coarse aggregate, then add it to a 2-5% (w / w) γ-aminopropyltriethoxysilane solution and soak for 160-180 minutes. After soaking, transfer the coarse aggregate to a drying equipment and dry it at 50-60℃. A nano-calcium carbonate suspension with a mass concentration of 1-5% was sprayed onto the surface of the dried coarse aggregate. The nano-calcium carbonate suspension also contained sodium hexametaphosphate with a mass concentration of 0.5-1%. After spraying, the coarse aggregate was allowed to air dry naturally.

7. The low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag according to claim 1, characterized in that: The water-reducing agent comprises, by weight, 30-40 parts of polycarboxylate-based water-reducing agent mother liquor, 5-10 parts of sodium gluconate, 10-15 parts of sodium lignosulfonate, and 35-45 parts of water.

8. A method for preparing low-carbon concrete based on the comprehensive utilization of high-quality sand and lithium slag as described in any one of claims 1-7, characterized in that: Includes the following steps: Mix coarse aggregate and fine sand for 1-2 minutes, then add cement, stone powder and lithium slag, and mix for 5-10 minutes to obtain dry material. Add water-reducing agent and water to the dry material and mix for 10-15 minutes.